THE ABILITY OF Lactobacillus plantarum BSL IN REDUCING THE TISSUE DAMAGE OF LIVER AND SPLEEN IN RATS INFECTED BY Listeria monocytogenes ATCC 7644 - Firat Meiyasa; Betty Sri Laksmi Jenie; Lilis Nuraida; Nurbety Tarigan (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2019)
Lactobacillus plantarum BSL, previously isolated from Indonesian sauerkraut. In this study, we investigated the ability of L. plantarum BSL in reducing the tissue damage of liver and spleen in rats infected by Listeria monocytogenes ATCC 7644. Treatment group of rats received 0.5 mL culture suspension (109 CFU/mL) of L. plantarum BSL and control group received 0.5 mL of 0.85% w/v NaCl daily for nine days of experiment. Both groups were infected at 3rd day with 0.5 mL of suspension of L. monocytogenes (109CFU/mL). At the 2nd (before infection), 5th, 7th, and 9th day (after infection), the rats were sacrificed and then, liver and spleen were assessed for histopathological. Our study revealed that the administration of L. plantarum BSL could be able to reduce the liver and spleen damage of the experimental rats.